2014
DOI: 10.1007/s10980-014-0113-0
|View full text |Cite|
|
Sign up to set email alerts
|

What is the role of trees and remnant vegetation in attracting people to urban parks?

Abstract: Public parks commonly contain important habitat for urban biodiversity, and they also provide recreation opportunities for urban residents. However, the extent to which dual outcomes for recreation and conservation can be achieved in the same spaces remains unclear. We examine whether greater levels of (i) tree cover (i.e. park 'greenness') and (ii) native remnant vegetation cover (i.e. vegetation with high ecological value) attract or deter park visitors. This study is based on the park visitation behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 75 publications
4
67
0
3
Order By: Relevance
“…the plants that we sampled. Previous studies support our assumption and the perception of urban green space has often focused on conspicuous plants (Fuller et al 2007;Dallimer et al 2012;Shwartz et al 2014;Carrus et al 2015;Shanahan et al 2015). Moreover, vegetation cover was positively related to personal well-being in a study comprising 9 Australian towns and cities (Luck et al 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…the plants that we sampled. Previous studies support our assumption and the perception of urban green space has often focused on conspicuous plants (Fuller et al 2007;Dallimer et al 2012;Shwartz et al 2014;Carrus et al 2015;Shanahan et al 2015). Moreover, vegetation cover was positively related to personal well-being in a study comprising 9 Australian towns and cities (Luck et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Recent research in Brisbane, Australia, has shown that park visitors with stronger nature orientation traveled further and made longer visits than park users with a less pronounced nature orientation (Lin et al 2014). Moreover, park visitors with greater nature orientation tended to go to urban parks with higher levels of tree cover and remnant native vegetation and thus they were prepared to travel to such parks instead of using nearby parks (Shanahan et al 2015). Individual differences in perception of green space should thus be addressed when urban planners design city parks.…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to echo the complex relationships between people's preferences and perceived biodiversity values [55,56], under an apparent 'people-biodiversity paradox' [57]. In fact, the results for this paper echo other similar studies in which vegetation diversity was found to be moderately to very important [17,23,26] but contrasts with other studies that have identified negative preferences related to habitats of high plant species richness [56,58,59]. However, a moderate emphasis is given to animal species richness (7.8%, range by city, 6.8-9.5%), but even so, deserving a greater importance than in other studies [23,52,53].…”
Section: The Most and Least Preferred Public Green Space Characteristicssupporting
confidence: 73%
“…The analysis result of this study confirmed that people who live close to urban parks, green areas, religious institutions, and parkland tend to frequent involvement of physical activity. Another study conducted by Shanahan et al (2014) in Australia show usually tourists have been visiting parks near to their home than parks far from their home, which suggests that factors other than distance played a role. On the contrary, a UK based study conducted by Hillsdon et al (2006) show that there is no significant relationship between physical activity and green space availability as measured by distance and size of urban green spaces.…”
Section: Frequency Of Visit To Green Infrastructurementioning
confidence: 99%